The Effect of Employee Engagement Dimensions on Organizational Commitment in Small and Medium Enterprises in Indonesia - Yanti Mayasari Ginting; Paulus Perey Untajana; Anthoneta Kopong (International Journal of Management Science and Information Technology, 2026)
Employee engagement shapes the level of organizational commitment in small and medium-sized enterprises (SMEs) in Indonesia. Workers who form strong emotional connections to their responsibilities, actively assess their tasks, and participate consistently in daily operations tend to exhibit higher accountability and loyalty toward their organization. This study examines the relationship between emotional, cognitive, and behavioral engagement and organizational commitment among SME employees. A quantitative survey was conducted with 120 participants selected through purposive sampling. Data were gathered via a combination of online and in-person questionnaires. Analysis using SPSS included descriptive statistics, validity and reliability assessments, assumption testing, and multiple linear regression. Results indicate that all forms of engagement correlate positively with organizational commitment, with behavioral engagement showing the most significant impact. Employees who engage actively in their work demonstrate greater persistence in supporting organizational goals. These findings suggest that deliberate efforts to enhance engagement across multiple dimensions can strengthen stability and operational continuity in SMEs.